PENERAPAN STRATEGI PEMBELAJARAN AKTIF PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI KELAS VII MTs MA'ARIF NU 1 AJIBARANG KABUPATEN BANYUMAS - Reno Rezita Aprilia; Wahyu Sabilar R (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
This study aims to determine the application of active learning strategies in Islamic religious education subjects (PAI) in class VII MTs Ma'arif NU 1 Ajibarang Banyumas Regency. The importance of implementing active learning strategies in the learning process especially in Islamic Religious Education subjects is expected to reduce boredom or boredom in learners themselves. This type of research is field research. This study describes a process that occurs in the field in a descriptive form, while the approach used in this research is to use qualitative research. Data collection techniques using three techniques or triangulation, namely observation, interviews and documentation. The results showed that the application of active learning strategies in the PAI subjects conducted by MTs Ma'arif NU 1 Ajibarang Banyumas Regency was to adjust the subject matter, situation and conditions in learning. PAI teachers implement several active learning strategies namely, everyone is a teacher here (all can be teachers), card sort (sorting or choosing cards), team quiz (group quiz). This strategy is carried out as an effort of Islamic Religious Education teachers to provide convenience for students in understanding PAI lessons.